“POSSIBLE” OR “PROBABLE”. THE NEW APPROACH IN IDIOPATHIC PULMONARY FIBROSIS DIAGNOSIS - D. V. Petrov; S. N. Avdeev; O. V. Gaus; I. E. Stepanyan; I. E. Tyurin; A. L. Chernyaev; E. I. Shmelev (Вестник рентгенологии и радиологии)
The absence of any specific symptoms, variety of radiologic and histologic changes in lungs and often poor physicians experience are the reasons for difficulties in diagnostics of idiopathic pulmonary fibrosis. The diagnostic criteria are constantly being discussed. The basis of this article is The White paper of Fleischner Society (published in “The Lancet Respiratory Medicine” 2017).